Current status of assessment for accuracy characteristics of topocartographic products formation - Aukazhiyev, Zhanar; Ismailov, Erlan (Рroblems of engineering and professional education, 2023)
The complexity of land works due to the conditions of formation of the Earth’s surface as a result of probabilistic and empirical nature, characterized by a variety of structural construction. Today, this situation confirmed that the diversity of the plurality of elements and features of the Earth surface, interconnected allows you to represent the topographic surface as a random field heights, structured in the form of a complex geomorphological system